2023
DOI: 10.1155/2023/2925551
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms are Associated with More Negative Global Metacognitive Biases in Combat Veterans, and Biases Covary with Symptom Changes over Time

Abstract: Metacognitive awareness, insight into one’s abilities, is thought to be disrupted in depression and posttraumatic stress disorder (PTSD), with more negative metacognitive biases and reduced awareness, respectively. However, studies have rarely examined global aspects of metacognitive awareness in depression and PTSD, instead using task-specific measures. In 467 trauma-exposed post-9/11 veterans, we administered assessments of PTSD and depression, self-report and objective measures of cognitive functioning (neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…These relationships are observed in both "local" confidence judgments on individual trials [2][3][4] and "global" confidence as measured through long-run self-performance estimates 5 (which we refer to as global SPEs [6][7][8] ). Conversely, remission from depression symptoms, through either therapy or antidepressants, is found to ameliorate underconfidence 9,10 . However, previous studies examining the link between metacognition and symptoms have been descriptive, and a mechanistic understanding of why confidence distortions in anxious-depression persist despite otherwise intact performance remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…These relationships are observed in both "local" confidence judgments on individual trials [2][3][4] and "global" confidence as measured through long-run self-performance estimates 5 (which we refer to as global SPEs [6][7][8] ). Conversely, remission from depression symptoms, through either therapy or antidepressants, is found to ameliorate underconfidence 9,10 . However, previous studies examining the link between metacognition and symptoms have been descriptive, and a mechanistic understanding of why confidence distortions in anxious-depression persist despite otherwise intact performance remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…They further found that veterans with PTS and depression (which was prevalent in our sample) may have difficulty dealing with strong and negative emotions leading to symptom exaggeration. Furthermore, depression may further contribute to symptom exaggeration as negative cognitive biases may exacerbate symptom report (Agnoli et al, 2023; Armistead-Jehle, 2010; McCormick et al, 2013). Our findings highlight the need for clinical assessments, including the CAPS-4/5 and SCID-4/5, to also include separate validity measures as overreporting can bias findings.…”
Section: Discussionmentioning
confidence: 99%